Assessment of dysplasia in colorectal adenomas: an observer variation and morphometric study. - Brown, L J (1985)
Observer variation in the grading of dysplasia in 100 colorectal adenomas has been analysed by kappa statistics. Intraobserver agreement was only 70% and 67% for the two principal observers, and, as would be expected, interobserver agreement was even lower at 59% and 66%. Although the kappa values were significantly different from chance at the 0.1% level, there were substantial disagreements. When the study was extended to four observers, agreement between observer pairings was considerably worse (as low as 34%), and in four pairings the kappa values did not differ significantly from those expected by chance alone even at the 5% level. In an endeavour to improve agreement we adopted a percentage estimation grading method; but this failed to achieve any improvement when comparing overall grades. The percentage estimates of the two observers, however, showed a highly significant correlation. To identify the cytological features given most weight by the principal observers in assessing dysplasia we undertook morphometry on 30 adenomas using an image analysis computer. The nuclear to cytoplasmic ratio, variation in nuclear area, and variation in nuclear height above the basement membrane showed significant differences between mild, moderate, and severely dysplastic epithelia. While evaluation of these parameters therefore appears to be most important in the subjective interpretation of dysplasia, this study has shown that such evaluation is poorly standardised between observers and poorly reproduced within observers. Our findings of poor agreement in the grading of dysplasia in colorectal adenomas has serious implications for the assessment of dysplasia in inflammatory bowel disease, where the added problem of reactive cellular atypia brings greater complexity to these subjective judgments.